Physics of shock and impact. - Grady, D. E. (IOP (Series). Release 4., 2017)
Physics of Shock and Impact' deals with the shock physics of solids with emphasis on impact applications that are brought about intense energy stimulations. Comprising of two volumes, this work covers physical, material, mechanical and thermodynamic fundamentals of shock physics. The various chapters also include a range of analytic solutions that address topics in the many applications involving shock physics. Volume 2, 'Materials and shock response', addresses equation of state in the shockwave and the response to shock of various material classes.